Mechanism of Oxidation of (p-Substituted Phenylthio)acetic Acids with N-Bromophthalimide - N. M. I. Alhaji; A. M. Uduman Mohideen; K. Kalaimathi (E-Journal of Chemistry)
The kinetics of oxidation of (phenylthio)acetic acid (PTAA) by N-Bromophthalimide (NBP) in acetonitrile-water solvent mixture at 298 K in the presence of perchloric acid has been followed potentiometrically. The reaction is first-order each in NBP and PTAA and inverse fractional-order in H+. Also, it has been found that the reaction rate is not affected by changes in ionic strength of the reaction medium or by the addition of chemicals such as phthalimide, acrylonitrile and potassium bromide. However, an increase in the water content of the solvent mixture causes an increase in the rate of reaction. These observations have been well analyzed in favour of a SN2-type mechanism, involving NBP itself as the reactive species. Effect of substituents on the reaction rate has been analysed by employing various (p-sustituted phenylthio)acetic acids. The electron-releasing substituent in the phenyl ring of PTAA accelerates the reaction rate while the electron-withdrawing substituent retards the rate. The excellently linear Hammett plot yields a large negative ρ value, supporting the involvement a bromosulphonium ion intermediate in the rate-determining step.